Urban transformation towards smart cities - Khalid Zainab (E3S Web of Conferences)
Smart cities have been considered as a focal point in many research and fields of study, and a major target for national, international policies, and strategies including the urban aspects; Is the smart city a reality or an ambition by researchers. As the world’s population increases and the demands resulting from the expansion and growth of urbanization increase, architects and urban engineers face economic, political, social, and technological challenges to solve problems, Population increases that have stressed the burden on the urban structure and increased the consumption of resources. It is necessary to strengthen existing cities as they are a powerful engine for economic growth and sustainable development. Hence, the research question emerged about the possibility of transforming existing cities into smart cities. The research turned to solving the research problem by analyzing international examples of smart cities and benefiting from their experiences. In the results make, discuss and assess Baghdad City Readiness checklist for Transformation towards Smart Cities. research concluded that the city is a physical place that can be the site of digital and sustainable projects with a set of indicators to transform current cities into smart cities.